Carbohydrate and sleep: An evaluation of putative mechanisms - Benton, David; Bloxham, Anthony; Gaylor, Chantelle; Brennan, Anthony; Young, Hayley A. (Frontiers in Nutrition, 2022)
Sleep problems are extremely common in industrialized countries and the possibility that diet might be used to improve sleep has been considered. The topic has been reviewed many times, resulting in the frequent suggestion that carbohydrate increases the uptake of tryptophan by the brain, where it is metabolized into serotonin and melatonin, with the suggestion that this improves sleep. However, as the credibility of these mechanisms has tended not to have been critically evaluated, they were considered by examining their biochemical, nutritional, and pharmacological plausibility. Although high carbohydrate consumption can increase the uptake of tryptophan by the brain, it only occurs with such low levels of protein that the mechanism is not relevant to a normal diet. After entering the brain tryptophan is converted to serotonin, a neurotransmitter known to influence so many different aspects of sleep and wakefulness, that it is not reasonable to expect a uniform improvement in sleep. Some serotonin is converted to melatonin, although the exogenous dose of melatonin needed to influence sleep cannot be credibly provided by the diet. An alternative mechanism was proposed based on animal literature that has been largely ignored by those considering diet; it was relevant as after consuming a lower amount of carbohydrate, more time is spent in slow-wave sleep, and less in rapid-eye-movement sleep. Sleep and energy homeostasis are closely connected, and in the hypothalamus, glucose-sensing neurons trigger physiological responses that help to maintain glucose homeostasis, a mechanism associated with changes in the stages of sleep. The suggestion was examined that carbohydrate-induced changes in the level of blood glucose influence different stages of sleep, paying particular attention to the functioning of the hypothalamus.. This review was registered in the International Prospective Register of Systematic Reviews (CRD42020223560).